THE ROLE OF COOPERATIVE PRINCIPLE IN THE CREATION OF NARRATIVE JOKES IN JOKELOPEDIA: THE BIGGEST, BEST, SILLIEST, DUMBEST, JOKE BOOK EVER! - TEMARA, ODYSIUS BIO (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cooperative Principle, Conversational Maxims, Humor, Jokelopedia. In human communication, the participants must speak cooperatively to be understood in a particular way. The cooperative principle, along with the four conversational maxims, describes how effective and efficient communication in conversation is achieved. However, comedians often purposefully flouted these maxims for the humorous effect of their story. The writer conducted a study about the role of cooperative principle, more specifically, the flouting of conversational maxims in the creation of humor in narrative jokes in Jokelopedia: The Biggest, Best, Siliest, Dumbest, Joke Book Ever!. This study aims at finding out the flouted maxims in the narrative jokes, the implicature in the narrative jokes, and how the implicature is expected to create humorous effect in the narrative jokes.This study focuses on the flouting of conversational maxims in three chapters with the most number of narrative jokes in Jokelopedia. This study uses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. Descriptive study in textual analysis is applied in this study to analyze the narrative jokes in the book.This study reveals that all conversational maxims are flouted in order to create humorous effect in the narrative jokes. From 40 narratives analyzed by the researcher, maxim of relation is the mostly flouted maxim with 15 occurrences.The maxim of quantity is the second with 10 occurrences. Then, the maxim of quality and manner are the least flouted maxims with 9 and 6 occurrences. These flouting of conversational maxims gives access to hidden meanings called implicature with which humorous effect is generated. Mostly, the implicature is expected to create humorous effect by showing a contrast between the development of the reader’s expectation and the fact in the story, or by showing the foolish or inappropriate behavior of the characters.The conclusion of the study shows that humor can be invoked by the flouting of conversational maxims. In addition, the emergence of the humor caused by the flouting of maxims also depends on the interpretation of the readers and their encyclopedic knowledge. The writer suggests future researchers to use other theories such as Leech’s politeness principle or Sperber & Wilson’s relevance theory, to find other materials such as visual and auditory media as the source of data, and to analyze the humorous effect which is not caused by the flouting of conversational maxims.